Making of Hero : four brothers, two wheels and a revolution that shaped India - Munjal, Sunil Kant (Noida Harper Collins Publishers, 2020)
From the by lanes of Kamalia and the rugged landscapes of Quetta in India of the 1940s and what became Pakistan, they escaped to the Partition-ravaged cities of Amritsar, Agra and Delhi, with little more than the shirts on their backs. From here, four of the six Munjal Brothers built their business, part by part. There was no grand vision of building a world-scale enterprise; their aim was simply to survive. Hero began with trading and then manufacturing bicycle parts, evolved into bicycles, mopeds, automotive parts and motorcycles & scooters, and today Hero and its successors encompass service businesses and infrastructure. Thirty years after starting, Hero Cycles became the world s largest bicycle maker in 1986. In the next fifteen years, in 2001, the motorcycle venture became the world s largest, and both pole positions are held firmly even today. This is an authentic Make in India story about overcoming many odds: the ravages of time, global competition and even business history. It follows the lives of the four Munjal brothers who lived together and scripted a revolution on two wheels without any formal education or resources. In parallel, it s also the story of how India s agrarian economy, with limited means of transportation, took wings on this two-wheel revolution. Driven by family values and Indian wisdom, yet pioneering in its thinking and best practices, Hero firms today are renowned for placing mutually beneficial relationships at the core of their business philosophy.
Keywords: Automobile industry and trade - India